Innovative work behavior in high-tech enterprises: Chain intermediary effect of psychological safety and knowledge sharing - Xu, Ziqing; Suntrayuth, Sid (Frontiers in Psychology, 2022)
In several studies, innovative work behavior is witnessed as one of the keys to a long-term competitive edge for high-tech enterprises. This study examines the effect of organizational innovation climate on innovative work behavior. It attempts to build a chain intermediary effect model to explore the internal mechanism through which organizational innovation climate influences R&D employees’ psychological safety and knowledge sharing and the differences in the effects of different influencing paths. Using the data of 446 R&D employees from high-tech enterprises in Guangdong, China, the results indicated that, at first, organizational innovation climate was positively correlated with psychological safety and innovative work behavior. Psychological safety was positively correlated with innovative work behavior. Knowledge sharing was significantly and positively correlated with innovative work behavior. Second, Psychological safety and knowledge sharing play a significant mediating role in the relationship between organizational innovation climate and innovative work behavior, and psychological safety further improves individual innovative work behavior by influencing knowledge sharing among research team members.